Atypical Presentation of Lateral Periodontal Cyst in an Elderly Female Patient – A Rare Case Report - Castelino, Renita Lorina; Rao, Kumuda; Bhat, Supriya; Babu, Subhas Gogineni (UI Scholars Hub, 2016)
elderly, lateral periodontal cyst, odontogenic cyst, residual cyst